Second Five Year Plan Delhi - Planning Commission (Planning Commission)
The process of planned economic development was initiated in India more than ten years ago. The central objective of the planning undertaken has been the promotion of rapid and balanced economic development with a view to raise the living standards of the people and to establish a socialist pattern of society. The First Five Year Plan was calculated to strengthen the economy at the base and to initiate institutional changes which would facilitate more rapid advance in future. The Second Five Year Plan was intended to carry forward and accelerate the process of development initiated in the First Plan period.
An Appraisal